Traditional dance preservation model through mobile game design: a case study of Riau Malay persembahan dance - Setiawan, Panji Rachmat; Syefriani, Syefriani; Mohamad Yatim, Maizatul Hayati; Wandri, Rizky (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
The rapid erosion of intangible cultural heritage, exemplified by the declining engagement of youth with the Riau Malay Persembahan Dance, poses an urgent challenge to the continuity of regional identity and values. This research responds by developing a mobile game designed to preserve and revitalize this traditional dance through digital media. The study employs a structured Research and Development (R&D) methodology integrated with the Game Development Life Cycle (GDLC), ensuring both scientific rigor and authentic cultural representation. Game design and development involved iterative prototyping, expert validation, and user testing, with data collected via structured surveys, interviews, and direct observation. The game was evaluated by 35 participants from diverse backgrounds, whose feedback demonstrated high levels of engagement and cultural appreciation. Statistical analysis using a chi-square test (X2=399.25, df=3, p<0.0001) confirmed overwhelmingly positive reception, with 85% of participants reporting increased interest in Riau Malay culture after gameplay. Despite limitations such as platform exclusivity and a narrow cultural focus, the results underscore the game’s effectiveness as an educational tool and its potential for broader implementation. This research contributes a replicable model for digital cultural preservation, demonstrating that interactive media can significantly enhance the transmission and appreciation of intangible heritage among younger generations.